COMPARISON OF THE VALUE OF INFLAMMATION MARKERS AND HEART REMODELING PARAMETERS IN PATIENTS WITH DISTINCT TYPES OF ATRIAL FIBRILLATION - L. G. Azarapetyan; S. V. Grigoryan; K. G. Adamyan (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To compare the influence of the most informative parameters of inflammatory markers and structural-geometrical parameters of the heart remodeling in patients with different clinical types of atrial fibrillation (AF). Material and methods. We observed 141 patients with ischemic heart disease (CHD) and arterial hypertension (AH) having nonvalvular type of AF. Duration of AF was up to 84 months, mean 13,8±8,0 months. As controls we examined the same by age and gender patients with CHD and AH, however without AF — 18 patients. All patients underwent clinical and instrumental, immunological investigation. Mathematical processing was done with SPSS-13.Results. By the cluster-analysis method we found that except the remodeling parameters in paroxysmal and persistent AF important role do play the levels of such markers as C-reactive protein (C-r.p.) and inlerleukine-6 (IL-6). In patients with permanent form of atrial fibrillation inflammation markers levels do not play key role. Conclusion. C-r.p. and inflammatory cytokines play some role in pathogenesis of AF, especially in its paroxysmal and persisting types. And as C-r.p., being an acute phase protein, cannot be the specific marker of inflammation in AF, but the increase of C-r.p. might be the predictor of IL-6 level increase, especially in paroxysms and returns of Af.